Synthesis, COSMO-RS analysis and optical properties of surface modified ZnS quantum dots using ionic liquids - Shahid, R. (Elsevier Ltd, 2015)
Zinc sulfide (ZnS) quantum dots (QDs) were synthesized using the microwave assisted ionic liquid (MAIL) route. Three ionic liquids (ILs), namely, 1-butyl-3-methylimidazolium tetrafluoroborate (BMIMBF4), trihexyl(tetradecyl) phosphonium bis(trifluoromethanesulfonyl) amide (P6,6,6,14TSFA) and trihexyl(tetradecyl) phosphonium chloride (P6,6,6,14Cl) were used in this study. The size and structure of the QDs were characterized by high-resolution transmission electron microscopy (HR-TEM) and selected area electron diffraction (SAED) pattern, respectively. The synthesized QDs were of wurtzite crystalline structure with size less than 5 nm. The QDs were more uniformly distributed while using the phosponium based ILs as a reaction medium during synthesis. The optical properties were investigated by UV-vis absorption and photoluminescence (PL) emission spectroscopy. The optical properties of QDs showed the quantum confinement effect in their absorption and the effect of cation and anion structural moiety was observed on their bandedge emission. The QDs emission intensity was measured higher for P6,6,6,14Cl due to their better dispersion as well as high charge density of Cl anion. The capability of the ILs in stabilizing the QDs was interpreted by density functional theory (DFT) computations. The obtained results are in good agreement with the theoretical prediction. Â© 2015 Elsevier Ltd.